Application of the Value Clarification Technique Method to Improve the Internalization of Students' Akhlakul Karimah Values at MA Yapis Al-Oesmaniyyah - Imam Faqih (Journal of Action Research in Islamic Education, 2025)
This study aims to improve the internalization of Akhlakul Karimah (noble character) values among students through the application of the Value Clarification Technique (VCT) method at MA Yapis Al-Oesmaniyyah. The research employed a Classroom Action Research (CAR) design conducted in two cycles, involving 32 eleventh-grade students. Each cycle consisted of planning, action, observation, and reflection stages. Data were collected through observation sheets, value internalization questionnaires, reflective journals, and documentation. Quantitative data were analyzed using descriptive statistics to measure the improvement of students’ internalization scores, while qualitative data were analyzed through thematic reflection to capture behavioral changes. The results indicate a significant improvement in students’ internalization of Akhlakul Karimah values after the implementation of VCT. The average pre-action score was 61.84 (moderate category), which increased to 74.37 in Cycle I and further improved to 86.12 in Cycle II (high category). The percentage of students achieving the predetermined mastery criterion (≥75) increased from 34.38% in the pre-cycle to 65.63% in Cycle I and 90.63% in Cycle II. Observational data also revealed notable improvements in students’ honesty, responsibility, discipline, respect, and empathy during classroom interactions. The reflective process demonstrated that VCT encouraged students to critically examine moral dilemmas, articulate personal values, and commit to consistent moral behavior. The findings confirm that the Value Clarification Technique method is effective in fostering deeper moral value internalization in Islamic Religious Education. This study contributes empirically to innovative pedagogical approaches for strengthening character education within Islamic secondary schools and supports the integration of reflective-value-based learning strategies to promote sustainable moral development.